Gold coordination during homogeneous alkyne and allene cyclisation catalysis: Coordination to substrates, to ancillary ligands and in intermediates - Helgard Raubenheimer; Hubert Schmidbaur (South African Journal of Science, 2011)
The ever-increasing role of homogeneous gold catalysis in organic synthesis and the consequent need to be able to rationally control the rate and outcome of such reactions has emphasised the importance of each successive metal - carbon coordination step. Concentrating on alkyne and allene cyclisation and upon reaction mechanisms postulated on the basis of empirical and theoretical results, we have examined the coordination of gold fragments to triple bonds, the modification of gold(I) precatalysts to effect specific reaction pathways or enantioselectivity and the isolation of coordinated intermediates or model compounds thereof. Some of the recent advances that have been made in various laboratories are described in this compact review.